Relationship between Corporate Governance and Risk Disclosure Practice from Malaysia Perspective - Riyard Bin Kiflee, Ag Kaifah; Noor Azli Bin Ali Khan, Mohd (KnE Social Sciences, 2019)
Past accounting scandals (Transmile and Megan Media) and recent 2007/2008 global financial crisis have triggered the need for vibrant risk management and high quality of risk reporting through sound corporate governance. This study will measure risk management through the disclosure in the annual reports. It wishes to determine the presence of risk information within the annual report of non-financial companies in Malaysia. The objective of the study is to examine the relationship between corporate governance characteristics and risk disclosure practice. The corporate governance characteristics examined include board independence, the board size, board gender, auditor independence and auditor tenure. A total of 721 companies are expected to be analyzed based on the Bursa Malaysia list from 2008 to 2017. To determine the level of risk disclosure, this study will employ content analysis. Descriptive statistics and multiple regression will be used in this study to examine this relationship.